Is L-lactate a novel signaling molecule in the brain? - Mosienko, Valentina (J Cereb Blood Flow Metab, 2015)
In the brain, L-lactate is produced by both neurons and astrocytes. There is no doubt that neurons use L-lactate as a supplementary fuel although the importance of this energy source is disputed. Irrespective of its caloric value, L-lactate might also have a signaling role in the brain. Here, we review several current hypotheses of L-lactate mediated signaling. Some proposed mechanisms require L-lactate entry into the neurons leading to a shift in ATP/ADP ratio or redox state. Others postulate interaction with either known receptor HCA1 (GPR81) or a novel, yet unidentified receptor. We argue that the sensitivity of any such mechanism has to match the concentration range of extracellular L-lactate, which is less than ~1.5 mmol/L under physiologic conditions. From that point of view, some of the proposed mechanisms require supraphysiologic levels of L-lactate and could be engaged during ischemia or seizures when L-lactate concentration rises dramatically. Currently, we do not know whether L-lactate production in the brain occurs in microdomains, which might create higher than average local concentrations. Nevertheless, it is clear that in the brain, as in the peripheral tissues, L-lactate is not only used as a source of energy but also acts as a signaling molecule.